2020
DOI: 10.3390/vaccines8020310
|View full text |Cite
|
Sign up to set email alerts
|

Lipidation of Pneumococcal Antigens Leads to Improved Immunogenicity and Protection

Abstract: Streptococcus pneumoniae infections lead to high morbidity and mortality rates worldwide. Pneumococcal polysaccharide conjugate vaccines significantly reduce the burden of disease but have a limited range of protection, which encourages the development of a broadly protective protein-based alternative. We and others have shown that immunization with pneumococcal lipoproteins that lack the lipid anchor protects against colonization. Since immunity against S. pneumoniae is mediated through Toll-like receptor 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Recent clinical trials have now reported the strong protective effect of T-cell-inducing vaccines against a range of diseases, including HIV, malaria, influenza, tuberculosis, and cancer [ 76 ]. On the contrary, vaccination of mice with lipidated pneumococcal lipoproteins enhanced antibody-mediated immunity compared with vaccination with non-lipidated proteins, but had no significant effect on the CMI responses [ 77 ]. Another possibility is caused by ORF7 , which is involved in A2.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have now reported the strong protective effect of T-cell-inducing vaccines against a range of diseases, including HIV, malaria, influenza, tuberculosis, and cancer [ 76 ]. On the contrary, vaccination of mice with lipidated pneumococcal lipoproteins enhanced antibody-mediated immunity compared with vaccination with non-lipidated proteins, but had no significant effect on the CMI responses [ 77 ]. Another possibility is caused by ORF7 , which is involved in A2.…”
Section: Discussionmentioning
confidence: 99%
“…All tested pneumococcal lipoproteins were heterologously expressed without the lipid moiety. The naturally occurring lipidation of lipoproteins has been shown to trigger TLR2-dependent signaling in leukocytes [ 178 , 179 ]. Therefore, lipidated proteins were tested in comparison to their non-lipidated forms [ 179 ], but no activation leading to P-selectin surface staining was detected.…”
Section: Platelets In S Pneumoniae Infectionsmentioning
confidence: 99%
“…The naturally occurring lipidation of lipoproteins has been shown to trigger TLR2-dependent signaling in leukocytes [ 178 , 179 ]. Therefore, lipidated proteins were tested in comparison to their non-lipidated forms [ 179 ], but no activation leading to P-selectin surface staining was detected. Nevertheless, it is noteworthy to know that TLR expression levels in resting platelets is low, but they become upregulated, and levels increase on the platelet surface upon activation [ 87 , 180 ].…”
Section: Platelets In S Pneumoniae Infectionsmentioning
confidence: 99%
“…Further, it was reported that the lipidated pneumococcal antigens (DacB and PnrA) have shown ameliorated humoral immune responses when administered in mice. Compared to non‐lipidated proteins, the lipidated modified protein was responsible for the induction of high antibody titers, hence accountable for suppressing Pneumococcus colonization (Voß et al, 2020 ).…”
Section: Posttranslational Modifications In Vaccine Candidatesmentioning
confidence: 99%